The Influence of Social Media and Online Shopping Habits on Consumer Behavior and Social Identity in Indonesia’s Digital Economy - Hendrayani, Eka; Prawirosumarto, Suharno; Lusiana, Lusiana; Putra, Roni Syah (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
This study aims to examine the impact of social media and online shopping habits on consumer behavior and social identity within the context of Indonesia’s digital economy. The research analyzes how social media and online shopping habits influence consumer behavior and social identity within the framework of Indonesia’s digital economy. A quantitative methodology was employed, collecting data from 280 participants using a Likert-scale questionnaire, and Structural Equation Modeling with Partial Least Squares (SEM-PLS) was applied to test the relationships. The findings reveal that social media influence and online shopping habits significantly affect consumer behavior and social identity. Furthermore, consumer behavior and social identity were found to strongly contribute to the growth of the digital economy. These results highlight the crucial role of digital platforms in shaping consumer actions and identities, thereby driving Indonesia’s digital economy. This study provides practical insights for business practitioners to leverage social media and e-commerce to influence consumer behavior and for policymakers to promote supportive digital infrastructure.